OP0190-PC Prevalence and incidence of gout in italy. Analysis of a primary care database. (23rd January 2014) - Cavagna, L.; Trifirò, G.; Caporali, R.; Morabito, P.; Ferrajolo, C.; Pecchioli, S.; Simonetti, M.; Medea, G.; Cricelli, C.; Caputi, A.; Mazzaglia, G.; Montecucco, C.
Abstract : Background: Data from national surveys and general practitioner databases has shown an increasing prevalence of gout in several countries. However there is no data regarding the epidemiology of gout in Italy in the last decade. Objectives: To assess both prevalence and incidence of gout in Italy between 2005 and 2009. Methods: Data was obtained from the Italian primary care database (Health Search/Longitudinal Patient Database) which comprises about one million adults (>18 years) from all around the Country. Rates together with 95% Confidence Interval (CI) have been measured overall and stratified by age, gender and calendar year. Characteristics of patients with newly diagnosed gout and hyperuricemia have been explored Results: Calculated prevalence of symptomatic gout increased from 6.7 per 1, 000 adults in 2005 to 9.1 in 2009, whilst incidence remained stable (0.93 per 1, 000 Person Years (PYs) in 2005 and 0.95 in 2009). Prevalence increases with age and is 4 times higher in males. A similar trend was observed for hyperuricemia whose prevalence is about ten times higher than that of symptomatic gout (66.3 per 1, 000 adults in 2005 and 92.1 in 2009) in our population. Therefore during the study period, the prevalence of gout and hyperuricemia appears to be always slightly higher in the Northern Italy than in the Central and Southern Italy (e.g. year 2009: gout=9.3 vs. 8.6 vs. 9.0 per 1, 000 inhabitants; hyperuricemia=95.3 vs. 92.7 vs. 88.0 per 1, 000 inhabitants. Recurrent gout attacks were observed in 19.1% cases within one year following the first attack and in 23.1% cases within five years. Conclusions: This is the first study regarding the epidemiology of gout in Italy. The overall prevalence of both gout and hyperuricemia is remarkably lower than that reported in similar population-based investigations carried out in other western countries, namely the US, UK and Germany. This difference might in part be related to country specific diet; in fact the typical Italian diet (i.e. Mediterranean diet) is associated with low levels of serum urate. Interestingly, the prevalence of gout and, to a lesser extent, of hyperuricemia is quite different across Italian geographic areas, with the higher figures observed in the Northern Italy. This finding is likely to be attributed to different dietary habits as the adherence to Mediterranean diet is higher in Central and Southern than Northern Italy High recurrence of attacks was observed during the first year following the first episode. References: Roddy E, Doherty M. Arthritis Res Ther 2010;12:R223 Cea Soriano L, et al. Arthritis Res Ther 2011;13:R39 Zhu Y, et al. Arthritis Rheum 2011;63:3136-41 Annemans L, et al. Ann Rheum Dis 2008;67:960-6 Disclosure of Interest: None Declared